Pemberdayaan Masyarakat Desa Sukajaya Sumedang Selatan dalam Produksi Minuman Kesehatan dan Bumbu Rempah berbasis Teknologi Farmasi: Empowering the Sukajaya Village Community South Sumedang in the Production of Health Drinks and Spices based on Pharmaceutical Technology - Elya, Berna; Forestrania, Roshamur Cahya; Rahmasari, Ratika; Ariestanti, Donna Maretta; Nur, Syamsu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
As a result of observations and joint discussions with the Village Community, information was obtained that there are agricultural products in the form of spices with high annual production quantities. However, the selling value of these spices still needs to be improved. Technology has not touched them and has yet to be managed optimally. Therefore, the team empowers the community to process herbs into food products, namely health drinks and spices based on pharmaceutical technology. This activity aims to improve community welfare and mutual elements of human resources in the region. This activity was attended by 28 community members who are Partners and Village Officials. Social empowerment of the society involved in the downstream activities of agricultural products in Sukajaya Village will be carried out through socialization stages, FGD with society and village officials, establishing a micro business plan for downstream health drink products and spices building production facilities, and assistance. This activity produces products in spices, health drinks, and herbal candy. At least 80-90% of the community understands each stage of the activity so that it can become a provision for self-development. The output of this activity is in the form of innovative products, such as health drinks and spice products, which can increase partner empowerment.